Peningkatan Produksi Crude Palm Oil Melalui Kriteria Matang Panen Tandan Buah Segar untuk Optimalisasi Pendapatan Perusahaan - Sitorus, Mastarida L. F.; Akoeb, Erwin Nyak; Sembiring, Rasmulia; Siregar, Muhammad Akbar (AGRISAINS: Jurnal Ilmiah Magister Agribisnis, 2020)
This study aims to determine the maturity level of oil palm fresh fruit bunches (FFB) that enter the Palm Oil Mill (POM). If the maturity level of FFB changes (not standardized), the company's income will change. This research method uses a quantitative approach, the type of research is secondary data collection. Data were obtained from POM of Rambutan PTPN III with garden samples, namely the Raja Tanah Gardens, Sei Putih, Sarang Giting, and Rambutan. The data collected is secondary data in the form of data series, namely FFB production, CPO, Core and Revenue in 2016 - 2018. Data were analyzed using multiple linear regression, optimization and two different test averages. The results showed that the composition of harvested fruit had a very significant effect on CPO and core production. Optimizing the maturity of the fruit harvest will significantly increase the production of palm oil and palm kernel. The average palm oil production that can be optimized from the realization in accordance with the fruit maturity criteria is 4,734.16 tons or 11.04%. The average palm kernel production that can be optimized from the realization in accordance with the fruit maturity criteria is 1,091.31 tons or 11.54%. Optimizing the maturity of harvested fruit will significantly increase revenues from palm oil and palm kernel. The average income that can be optimized from optimizing palm oil production is Rp. 38,862.51 million or 11.14%. The average income that can be optimized from optimizing the production of Palm Oil is Rp. 7,350.05 million or 11.57%